FRI0049 Are there differences between young and older onset early rheumatoid arthritis (RA) and does this impact outcomes? an analysis from the catch cohort. (23rd January 2014) - Arnold, M.; Bykerk, V. P.; Haraoui, B. P.; Boire, G.; Hitchon, C.; Thorne, C.; Keystone, E.; Pope, J. E.
Abstract : Background: The population is ageing and the median age of rheumatoid arthritis onset is also increasing. There may be differences in the manifestations of early RA (ERA) onsetting in the elderly compared to younger patients. Current literature varies when considering the impact of age on outcome in RA. Objectives: This study was designed to compare ERA in elder onset vs. the other patients using data from a large multi-site cohort. Methods: Data from the Canadian Early Arthritis Cohort (CATCH) were examined at 0, 6 and 12 month visits. Patients were divided into three groups based on age. Logistic regression was done to determine the influence of age, baseline DAS28 and gender on remission at 12 months. Results: Of 1809 patients assessed at baseline, 442 (24.4%) were considered 'young' (<42 years), 899 (49.7%) were considered 'middle-aged' (42 between 64 years) and 468 (25.9%) were considered 'old' (>64 years). A significant correlation exists between age and DAS28 at baseline and 12 months, DAS28 remission at 12 months, HAQ at baseline and presence of erosions where an increase in age leads to a worse outcome in each case. At baseline, 72.9% were female, 63.8% met 2010 ACR/EULAR Classification Criteria for RA, symptom duration at first visit was 186.0 days, DAS28 was 4.9, HAQ score was 1.0, 25.3% had presence of erosions and 7.1% were in DAS28 remission. When evaluating for an increase in age, the number of females decreased (P < 0.000), proportion that met 2010 ACR/EULAR Classification Criteria for RA increased (P < 0.000), symptom duration at first visit decreased (P < 0.000), DAS28 increased (P < 0.000), HAQ increased (P < 0.001), proportion having presence of erosions increased (P < 0.000) and proportion in DAS28 remission decreased (P < 0.003). Although the means in all groups improved, there was no significant between groups difference in DAS28 and HAQ from 0-12 months. DMARD treatments and many varying comorbidities increased with age, while biologics treatment decreased with age. In the binary logistic regression model, gender had a large influence on the proportion of patients in DAS28 remission at 12 months with females having a much lower chance of remission. Table of results: Conclusions: Older onset RA patients start and end worse in terms of functional ability, disease activity and radiological damage than younger patients, however there are no differences in response to treatment. Gender appears to have a large effect on the outcome in RA patients. Disclosure of Interest: M. Arnold Grant/research support from: Summer studentship from the Canadian Rheumatology Association Roche Summer Studentship, V. Bykerk: None Declared, B. Haraoui: None Declared, G. Boire: None Declared, C. Hitchon: None Declared, C. Thorne: None Declared, E. Keystone: None Declared, J. Pope Grant/research support from: The CATCH study was designed and implemented by the investigators and financially supported initially by Amgen Canada Inc. and Pfizer Canada Inc. via an unrestricted research grant since inception of CATCH. As of 2011, further support was provided by Hoffmann-La Roche Ltd., United Chemicals of Belgium (UCB) Canada Inc., Bristol-Myers Squibb Canada Co., Abbott Laboratories Ltd., and Janssen Biotech Inc. (a wholly owned subsidiary of Johnson & Johnson Inc.).